2019
DOI: 10.1620/tjem.249.143
|View full text |Cite
|
Sign up to set email alerts
|

High Serum Cortisol Levels as a Potential Indicator for Changes in Well-Regulated Daily Life among Junior High School Students

Abstract: Problematic smartphone use among adolescents has become a social concern and is associated with poor sleep quality. The relationship between life habits, such as smartphone use and sleep duration, and levels of immunological and neuroendocrine biomarkers, including the stress hormone cortisol, in adolescents seems to be important to objectively comprehend their health and well-being in school life. However, such a relationship has not been well documented. We therefore studied rural junior high school students… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…The presence of stress in students during the period of climatic and social adaptation was evidenced by increased levels of cortisol. These findings were in agreement with those obtained by other researchers who noted that the level of cortisol is directly linked to stress and anxiety that students experience during exams [ 82 , 83 ], as well as to chronic lack of sleep in adolescents [ 84 ], and the effects of psychological and social stress in mentally unwell patients [ 85 ]. Previous studies noted that a higher level of cortisol is found in people whose profession is associated with increased risk and/or permanent stress, particularly police officers [ 86 ] and medics [ 87 ].…”
Section: Discussionsupporting
confidence: 93%
“…The presence of stress in students during the period of climatic and social adaptation was evidenced by increased levels of cortisol. These findings were in agreement with those obtained by other researchers who noted that the level of cortisol is directly linked to stress and anxiety that students experience during exams [ 82 , 83 ], as well as to chronic lack of sleep in adolescents [ 84 ], and the effects of psychological and social stress in mentally unwell patients [ 85 ]. Previous studies noted that a higher level of cortisol is found in people whose profession is associated with increased risk and/or permanent stress, particularly police officers [ 86 ] and medics [ 87 ].…”
Section: Discussionsupporting
confidence: 93%
“…A recent work con rmed that unhealthy lifestyle linked with high serum cortisol levels 29 . There were also high cortisol levels in pregnancy induced hypertension patients 30 .…”
Section: Discussionmentioning
confidence: 99%
“…), school attendance, and whether the individual is receiving needed outpatient care and taking his/her medication. Discussion looking at 3): typically use cortisol and amylase [4,5] as stress markers and chromogranin A as a mental stress marker.…”
mentioning
confidence: 99%